Petrodollars and imports of oil exporting countries - Roland Beck; Annette Kamps (European Central Bank (ECB), 2009)
This paper investigates the empirical determinants of import demand in oil exporting countries. Using a new dataset including a large cross section of oil exporting countries, we show with a panel cointegration analysis that import demand in these countries depends positively on domestic demand and exports, the real exchange rate and the price of oil. Fiscal surpluses, on the other hand, tend to reduce the demand for imports. More specifically, our import elasticities estimated for oil exporting countries are not far from estimates found in the literature on industrial countries. In particular, we conclude that the import elasticity with respect to domestic activity is larger than one – a finding which is in contrast to standard theoretical predictions but in line with most empirical findings for other countries. These results are robust over a wide set of alternative specifications.
Keywords: F14; F01; Q43; 330; Import Equation; oil exporting countries; Panel Cointegration; Importnachfrage; Preiselastizität; Panel; Kointegration; OPEC-Staaten